Zum Formwandel der Internationalisierung bei VW in den 80er und 90er Jahren - Haipeter, Thomas (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1999)
In the eighties and ninties a change in the form of internationalization took place which can be described as a step from multinational enterprise to a global integrated production network. The internationalization is part of a wider institutional context at the level of the enterprise. At Volkswagen, the global integrated production network replaced the old fordistic system of production by combining mass production with global flexibility.